Postsurgical dumping syndrome in a patient with gastric bypass: clinical case report - Hernández-Navas, Jorge Andrés; Dulcey-Sarmiento, Luis; Gómez- Ayala, Jaime; Therán-León, Juan; Toscano-Dulcey, Luis (Cirugía del Uruguay, 2025)
We report the case of a 42-year-old female patient with a history of gastric bypass surgery who presented with symptoms consistent with dumping syndrome, including sweating, palpitations, dizziness, and postprandial diarrhea. Paraclinical studies revealed a biphasic response in the oral glucose tolerance test, with early hyperglycemia followed by late hypoglycemia, as well as accelerated gastric emptying on radionuclide scintigraphy. Management included dietary modifications, such as meal fractionation, reduction of simple carbohydrates, and increased protein and fat intake, leading to clinical improvement. This case highlights the importance of early recognition of dumping syndrome and the implementation of nutritional strategies to enhance the quality of life of patients after bariatric surgery.